2023
DOI: 10.1371/journal.pone.0287536
|View full text |Cite
|
Sign up to set email alerts
|

Our good neighbors: Understanding ecosystem services provided by insectivorous bats in Rwanda

Olivier Nsengimana,
Faith M. Walker,
Paul W. Webala
et al.

Abstract: Bats are prodigious consumers of agricultural and forest pests, and are, therefore, a natural asset for agricultural productivity, suppressing populations of such pests. This study provides baseline information of diet of 143 bats belonging to eight insectivorous bat species from agricultural areas of Rwanda while evaluating the effectiveness of bats as pest suppressors. Using DNA metabarcoding to analyze bat fecal pellets, 85 different insect species were detected, with 60% (n = 65), 64% (n = 11) and 78% (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 82 publications
0
1
0
Order By: Relevance
“…Synanthropic insectivorous bats play a crucial role in the ecosystems of urban areas as they are natural controllers of agricultural pests [22,23]. In a recent study, Nsengimana et al determined that 60% to 78% of the diet of insectivorous bats consists of agricultural pests [24]. Aguiar et al calculated the value of pest suppression by synanthropic insectivorous bats and concluded that bats are saving USD 94 per hectare of cornfields and overall USD 390.6 million per harvest in Brazil [25].…”
Section: Discussionmentioning
confidence: 99%
“…Synanthropic insectivorous bats play a crucial role in the ecosystems of urban areas as they are natural controllers of agricultural pests [22,23]. In a recent study, Nsengimana et al determined that 60% to 78% of the diet of insectivorous bats consists of agricultural pests [24]. Aguiar et al calculated the value of pest suppression by synanthropic insectivorous bats and concluded that bats are saving USD 94 per hectare of cornfields and overall USD 390.6 million per harvest in Brazil [25].…”
Section: Discussionmentioning
confidence: 99%